Odpowiedź :
Szczegółowe wyjaśnienie:
1.
[tex]2.5a^{2} b*(-1,6)*a^{2} b^{2} =2.5a^{4} b^{3} *(-1,6)=-4a^{4} b^{3}[/tex]
-------------------------------------------------------------------------------------
2.
[tex]4x^{2} +7y+5x^{2} -7y+2=9x^{2} +2\\Odp. B[/tex]
-------------------------------------------------------------------------------------
3. a)
[tex]3a+7-4a+5+5a-2=4a+10\\\\dla\:\:\:\:a = -3\\\\4*(-3)+10=-12+10=-2[/tex]
b)
[tex]2x+2y+5-3x+3y=-x+5y+5\\\\dla\:\:\:\:x=3,\:\:\:y=-0,2\\\\-3+5*(-0,2)+5=-3+1+5=3[/tex]
-------------------------------------------------------------------------------------
4.
[tex]-5(2x+4y)=-5*2x+(-5)*4y=-10x-20y\\Odp. B[/tex]
-------------------------------------------------------------------------------------
5.
[tex]8(a-b)+a-8b=8a-8b+a-8b=9a-16b\\Odp.\:B[/tex]
-------------------------------------------------------------------------------------
6.
[tex](5x+6)(4-x)=20x-5x^{2} +24-6x=-5x^{2} +14x+24\\Odp.\:C[/tex]
-------------------------------------------------------------------------------------
7.
[tex]3a+(4a+1)=3a+4a+1=7a+1\\\\9n-3-(n-5)=9n-3-n+5=8n+2[/tex]
-------------------------------------------------------------------------------------
8.
[tex](x+2)^{2} +2(1-x)^{2} -(x+1)(x-1)=x^{2} +4x+4+2(1-2x +x^{2} )-(x^{2} -1^{2})=x^{2} +4x+4+2-4x+2x^{2}-x^{2} +1=2x^{2} +9\\\\dla\:\:\:\:x=\sqrt{2} \\\\2*(\sqrt{2}) ^{2}+9=2*2+9=13[/tex]